Exploring routines of leisure time mobility - Beckenbach, Frank; Briegel, Ramón; Scholl, Gerd; Konrad, Wilfried; Zundel, Stefan (Ökologisches Wirtschaften - Fachzeitschrift, 2010)
In Germany about 20 percent of CO2-emissions are caused by traffic. A considerable amount of this effect on the environment has to be assigned to mobility behaviour in the field of leisure time activities. What are the conditions to achieve a change in this field?